Exploring Efl Secondary Students’ Engagement In Reading Classroom Through Literature Circle - Muhamad Noor Fauzi; Muhammad Reza Pahlevi; Acep Bahrum Kamil (EduInovasi: Journal of Basic Educational Studies, 2024)
In reading classroom, students are required to comprehend text. One of its requirement is engagement as it is successful things in learning. However, one of recommended strategy is literature circle. Because a literature circle is strategies guide students to a deeper understanding of what they are reading through structured discussions about texts and books, and help students practice and develop the skills and strategies of being good readers. This study aims to investigate the students’ engagement of literature circles during the reading classroom. This is qualitative research with case study as a research design. To obtain data, observation, and interview were used for this research and then the obtained data was analyzed through thematic analysis. This research takes place in one of public junior high school in Telagasari and took several students from one class to interviews. There are three steps in the literature Circle, such as group discussion about books, they read books and discuss with the group and then find unfamiliar word. So we can solve the problem and find out the meaning of the word.